Simple Surgical Technique for Prevention of PPH at Cesarean Section - Iwo-Amah Rose Sitonma; K. O. Pepple Douglas; Ikiroma Sokeipirim Erasmus; Eli Sukarime (Current Progress in Medicine and Medical Research Vol. 9, 2023)
This chapter demonstrate the effectiveness of a quick surgical operation, while Primary postpartum hemorrhage can be avoided in women who are at risk by having a cesarean section. Pregnant women with placenta previa and previous cesarean section denote a very high-risk group of obstetric patients for major postpartum hemorrhage and peripartum hysterectomy. In women with scarred uterus the normal placental migration fails to occur, and the differential growth of uterine areas is hindered, contributing to high incidence of placenta previa in such cases. This study was conducted at the Rivers State University Teaching Hospital (RSUTH), Port Harcourt. It was a retrospective study of the intraoperative and postoperative blood loss in women who had cesarean section with predisposing factors for primary post-partum hemorrhage (PPH). After closure of the transverse lower segment incision on the uterus, the operator moves laterally to the left round ligament. An absorbable vicryl-2 suture on a round bodied needle is passed through the ligament, about 2 cm below the level of the uterine incision. The two edges of the suture are knotted together and cut about 1 cm from the knot. Application of purse-string compression sutures during cesarean section causes compres-sion of the uterus at the utero-cervical junction as well as vasoconstriction of the major uterine vessels as they ascend the lateral walls of the uterus. One thousand and five (1005) patients had this procedure done between 2014-2020. Their mode of delivery was cesarean section, and all of them had predisposing factors to primary postpartum hemorrhage. 997 (99.2%) had blood loss of <1000 ml. Only 8 (0.79%) had intraoperative and post-operative blood loss >1000 ml. These were due to extensive cervical lacerations and co-agulation disorders. It is suggested that the reduced blood loss in these women who were predisposed, was as a result of the purse-string suture during caesarean section. Reduced incidence of primary postpartum hemorrhage results in reduced incidence of maternal death due to this cause. When a woman has risk factors for primary postpartum hemorrhage and has a cesarean birth, purse-string compression suture (PSCS) is advised for use.